The Risk Factors of Recurrent Aphthous Ulceration among Patients in Misan Governorate (Indian Journal of Forensic Medicine & Toxicology, 2020)
Recurrent aphthous ulceration (RAU) is the most common oral mucosal disease which characterized byrecurrent episodes of multiple or solitary painful ulcerations without association with systemic diseases.The objectives of our study were to investigate the relation of RAU to demographical, education level andsmoking habit. The study was conducted on 120 patients, personal data (age, sex), site, level of educationand smoking habit were taken. The results showed that females were affected more than males, the buccalmucosa and tongue (58 %, 24%) respectively were the most common site of occurrence. There was higherprevalence rate of RAU among patients with higher educational level (60%) and in non-smokers (93.3%)